Use of agricultural wastes for the cultivation of Lentinus subnudus (Polyporales: Polyporaceae) in Nigeria - Fasidi, Isola O; Kadiri, Mukaila (Revista de Biología Tropical, 1993)
Lentinus subnudus a Nigerian edible mushroom is able to utilize a wide array of ligno-cellulosic wastes for vegetative growth and fructification. Of several substrates tested, Andropogon tectorum (Graminales: Grarnineae) straw produced the highest mycelial extension. Supplementing substrates with 1 0% and 30% rice bran or milled caslava peels improved mycelial extension (30% was optimum). Fructification occurred on 10gs oC Spondias mombin and unfermented compost comprising straw, rice bran, horse dung and CaS04'